Biological Nitrate Removal With Emerald Ash Borer-Killed Ash and High-Tannin Oak Woodchips - Wickramarathne, Niranga M.; Christianson, Laura E.; Foltz, Mary E.; Zilles, Julie L.; Christianson, Reid D.; Cooke, Richard A. C. (Frontiers in Environmental Science, 2021)
Two common tree species, ash (Fraxinus sp.) and oak (Quercus sp.), could provide readily available media for denitrifying bioreactors that use wood-based carbon for biological nitrate treatment. However, it is not known if the wood from Emerald Ash Borer-killed (EAB-killed) ash trees is an effective carbon source for nitrate removal compared to other wood species or if the high-tannin nature of oak inhibits denitrification potential. This lab-scale study showed that EAB-killed ash woodchips did not significantly differ in nitrate removal or denitrification potential compared to a commercially available blend of hardwood chips. However, neither treatment performed as well as oak woodchips in these metrics. Use of high-tannin oak in bioreactors is currently restricted by a federal standard in the United States. Ash woodchips beneficially exhibited the lowest nitrous oxide production potential, and their dissolved phosphorus leaching fell within the range of other woodchip types. Emerald ash borer-killed ash wood could be an effective source for denitrifying bioreactors located within affected regions and oak woodchips merit additional investigation for the application of denitrifying bioreactors.